Transformasi Integrasi AI Terhadap Pembelajaran Inklusif dan Multikultural dalam Era Digitalisasi Pendidikan - Subroto, Desty Endrawati; Runtu, Andro Ruben; Fahrudin, Ahmad; Langi, Jeffrey Payung; Arsyad, Muhammad (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This article aims to analyze the transformation of artificial intelligence (AI) integration in inclusive and multicultural learning in the era of educational digitalization. The study used a systematic literature review method on 35 scientific articles published in the period 2016–2026 and discussing AI in education, inclusive education, multicultural learning, assistive technology, AI literacy, algorithmic ethics, and generative AI. Article selection was carried out based on predetermined inclusion and exclusion criteria, then analyzed using thematic analysis through a process of grouping, coding, synthesizing, and interpreting key themes. The results of the study indicate that AI contributes to the transformation of learning through personalized learning, adaptive feedback, learning analytics, assistive technology, and expanding access to multicultural learning resources. On the other hand, AI implementation still faces challenges such as algorithmic bias, the digital access gap, low teacher AI literacy, and issues of privacy and ethical data use. These findings indicate that the success of AI integration is determined not only by technological advances, but also by teacher readiness, institutional governance, and the application of inclusive, multicultural, transparent, and ethical pedagogical principles. Therefore, AI needs to be positioned as a technology that supports, not replaces, the pedagogical role of teachers in creating equitable learning that values ​​diversity.